Effect of Topical Application of Black Seed Oil (Nigella Sativa) on Wound Healing in Diabetic Rat Ulcer Model - Eliza Arman; Almahdy A; Putri Dafiriani; Dedy Almasdy (Majalah Kedokteran Andalas, 2024)
Objective : This study aims to evaluate the use of topical black seed oil on wound healing in a diabetic rat model. Method:10 experimental rats were induced with streptozotocin at a dose of 55 mg/kg BW. Diabetic rats were anesthetized and then the wound was made with a biopsy push with a diameter of 10 mm. The rats were divided into 2 groups, namely the untreated group and the topical treatment group with 1 ml of 100% Black Seed Oil every day for 14 days. Wound healing evaluation was carried out on days 7 and 14. Gene expression analysis was performed using molecular technique RT PCR an histopathologically using He staining. Data analysis used T test. Result: On day 7 there was a decrease in TNF expression with p <0.05, while on day 14 it also showed a decrease in TNF alpha expression with p <0.01. Histopathological showed positive development by showing better wound healing with complete epithelialization, granulation with lower inflammatory cells, higher fibroblasts and collagen compared to the control group. Conclusion :Black seed oil can increase the speed of wound healing in diabetic rat models by inhibiting TNF alpha expression.